Exploring the Impact of Construction 4.0 on Industrial Relations: A Comprehensive Thematic Synthesis of Workforce Transformation in the Digital Era of Construction - Aso Hajirasouli; Ayrin Assadimoghadam; Muhammad Atif Bashir; Saeed Banihashemi (Buildings)
The rise of Construction 4.0—driven by digitalisation, automation, and data-intensive technologies—is radically reshaping the construction industry. While its technological innovations are widely acknowledged, their implications for industrial relations remain underexplored. In this study, we conduct a systematic literature review (SLR) of 91 peer-reviewed articles published between 2010 and 2024, aiming to synthesise emerging knowledge on how Construction 4.0 is transforming workforce dynamics, employment models, and labour relations. Using NVivo software and an inductive thematic approach, we identify seven key themes: workforce transformation, the attraction of new generations and women, skill requirements and workforce development, supply chain and logistics optimisation, digital twin technology in project management, the emergence of new business models, and safety and risk assessment. Our findings highlight both opportunities—such as improved collaboration, skill diversification, and enhanced productivity—and challenges, including job displacement, digital ethics, and widening disparities between developed and developing countries. Recent studies from 2023 and 2024 underscore routine-biased changes in workforce structure, evolving project management practices through digital twins, and critical skill shortages within the sector. Furthermore, contemporary policy shifts and increasing labour tensions in some regions reveal deeper socio-economic implications of digital construction. This review contributes to a more holistic understanding of how technological innovation intersects with social systems in the built environment. The insights presented offer valuable guidance for policymakers, educators, and industry leaders seeking to navigate the evolving landscape of Construction 4.0.